PENGGUNAAN MEDIA POSTER DALAM PEMBELAJARAN FISIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 2 KUANTAN HILIR SEBERANG - Fenni Sabzul Yaszak Sabzul Yaszak; Zuhdi Ma’aruf Ma’aruf; Yennita ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to determine improvement the learning outcomes cognitive science of physics by using media posters. This research was conducted in SMPN 2 Kuantan Hilir Seberang precisely in maret to June 2015. The subjects were students of class  VIIIA and VIIIC totaling 64 students consisting of two class which has been in both classes homogeneity testing. Form the research is pre-experimental with design intact-group comparison. The instrument of data collection in this research is a cognitive achievement test consists of 20 multiple choice items. Analysis of the data in this research is a descriptive analysis. The results were obtained absorption class using the media posters is higher then the class without using the media poster with a good enough category, otherwise learning effectiveness declared in effective less, then completeness of learning’s students classically and completeness of lesson declared not complete, and then improvement the learning outcomes cognitive students with a low category. Nevertheless, it can be concluded application media posters can increase the learning outcomes students class VIII SMPN 2 Kuantan Hilir Seberang in the subject matter vibration and wave. Key Words: Cognitive Learning Outcomes, Media Posters, vibration and wave